Poly-victimization reported by Chilean schoolchildren: is school a place to feel safe? (Innovaciones Educativas, 2022)
Exposure to episodes of violence, whether in the neighborhood, family or school, tends to be part of the daily lives of children and teenagers (NNA). In this sense, the objective of this article is to analyze the simultaneity and frequency of violent events reported by children and teenagers as victims, a phenomenon typified as poly-victimization. At the sample level, it makes use of the First National Polivictimization Survey applied to Chilean students between 7th grade and 3rd grade, applying a methodological design of an inferential statistical analysis and logistic regression, estimating the level of vulnerability and violence to which children and teenagers are exposed to and their protection and risk factors. Results show that participants claimed to have experienced victimization and poly-victimization, turning both problems into something transversal in the educational system. Common crimes and indirect victimization carried out by peers stand out, especially in witnessing attacks,  hittings, and threats. Conclusions highlight the need for comprehensive school measures as a crucial space for promoting healthy coexistence and violence rejection in any of its forms.
Keywords: child abuse; peaceful coexistence; poly-victimization; students; educational management; education